Planning of a Preventive Maintenance System for Lathe Machines Using the RCM II and FMECA - Fattah Fadjrir Adsa; Aulia Ishak; Anizar (Jurnal Sistem Teknik Industri, 2026)
Unplanned downtime and ineffective maintenance strategies remain major challenges in improving the reliability of production machinery in manufacturing industries. This study proposes a structured preventive maintenance system for a CW6293 lathe machine by integrating Reliability Centered Maintenance II (RCM II) and Failure Mode, Effects, and Criticality Analysis (FMECA). The novelty of this research lies in the systematic integration of risk-based criticality assessment, statistical reliability modeling, and maintenance task selection to develop an optimized maintenance framework. FMECA is employed to prioritize components based on severity, occurrence, and detection attributes, identifying the gearbox as the most critical component. Reliability analysis using Time Between Failure (TBF) and Time To Repair (TTR) data is conducted to determine appropriate maintenance intervals through Weibull and Normal distribution modeling. The RCM II decision logic is then applied to translate reliability characteristics and failure consequences into specific maintenance actions, namely scheduled discard and scheduled restoration tasks. This integrated approach enables the development of a proactive maintenance system that improves decision-making accuracy, enhances machine reliability, and supports a transition from reactive to risk-based preventive maintenance. The proposed framework demonstrates practical applicability for manufacturing environments and contributes to the advancement of maintenance engineering by combining reliability analysis, criticality evaluation, and structured maintenance policy design.